Improving Student Entrepreneurship Skills in Era Society 5.0 through Japik Minolasy Online Business - Emilia Denti; Meisy Haziza Putri; Meutia Rahma AN; Nurhalilah Tuljanah (CV. Media Inti Teknologi, 2023)
The development from the industrial era to the information age made significant changes. The very fast pace of information makes changes in both positive and negative directions. The positive thing about the development of the rate of information is marked by the ease of getting information. While the negative things from the development of the rate of information can damage humans because the information obtained is not good and can damage the mentality. The data analysis method in this study uses descriptive-qualitative analysis. Qualitative research is conducted to build knowledge through understanding and discovery, so that it is expected to be able to reveal various detailed and meaningful information, but also does not reject quantitative information in the form of numbers. In addition, it uses a descriptive approach that aims to provide an overview of student perceptions of the Japik Minolasy online business. Measurement of student perceptions was based on a Likert scale with a range of 1 to 5. By looking at the table of entrepreneurial skills and then calculating the percentage, the researcher got the percentage of skills before doing Japik Minolasy online business of 51.42%. This means that entrepreneurial skills are in the sufficient category. Then the percentage of skills obtained by researchers after running Japik Minolasy's online business increased to 85.71%. This shows that the scale obtained is very good. Determination of this scale based on Table 2 value criteria. An entrepreneur must be able to find good opportunities to do business and develop them properly. At that time required a variety of capabilities to support in order to produce something optimally. Some of these abilities we can call skills. From the results of the study, it appears that some of the skills possessed, both soft skills and hard skills, have increased before doing business and after doing business.